Peramalan Kebutuhan Obat Menggunakan Metode Single Exponential Smoothing - Amelia Vebrianti; Muhammad Nasir; Jemakmun Jemakmun; Andri Andri (Journal of Information System Research (JOSH), 2023)
Ogan Ilir Regional General Hospital (RSUD) tries to maintain the availability of medicines to meet patient needs. The Pharmacy Department of Ogan Ilir Regional Hospital always monitors existing drug stocks before placing orders with distributors of pharmaceutical supplies. The drug procurement process is carried out in a planned manner to reduce the risk of loss from the method of drug procurement and to identify the need for highly used drugs. This research aims to determine the forecasting of drug needs using the Single Exponential Smoothing method. The data used is drug use data for the period 2021 to 2022. Based on the research results, it was found that based on the highest MAPE score it was at 22% for alpha 0.1, and the highest MAPE was at 12% for alpha 0.5. These results show that the prediction of drug use is successful and has good value because the MAPE score does not exceed 20%.